Double ionophore application in cases with previous failed/low fertilization or poor embryo development. Issue 5 (May 2022) - Shebl, Omar; Reiter, Elisabeth; Enengl, Sabine; Allerstorfer, Christina; Schappacher-Tilp, Gudrun; Trautner, Philip Sebastian; Rechberger, Tamara; Oppelt, Peter; Ebner, Thomas
Abstract: Research question: Does a double ionophore application improve the outcome of cycles in which single ionophore application was unsuccessful? Design: This retrospective intervention study (duration 4.5 years) included 79 patients with suspected chronic failed oocyte activation (<30% fertilizations) and/or poor embryo development (developmental arrest, 24 h developmental delay, blastulation rate <15%) in both preceding cycles, the first without ionophore and the second with single ionophore treatment. Within the study period, all patients with failed ionophore treatments (single applications of ready-to-use calcimycin for 15 min) were offered an adapted protocol in the subsequent cycle (study cycle) in which the same ionophore was applied twice (separated by 30 min). Tests for paired data (control and study cycle) were used to reduce the effect of confounders. Results: The overall fertilization rate did not differ between the study and control cycles. Cleavage ( P = 0.020) and blastocyst formation ( P = 0.018) rates improved significantly in the study cycles. Implantation ( P = 0.001), biochemical ( P < 0.001) and clinical pregnancy ( P < 0.001) rates were also significantly higher in the study cycles. The study cycles resulted in 29 live births and all 32 babies born were healthy. Conclusions: This study suggests that double ionophore application may improve blastocyst formation and clinical pregnancy rates in cases of failed single ionophore treatment, irrespective of whether the ionophore was used to overcome fertilization failure or poor embryo development. Fertilization rate was only increased in cases with a history of fertilization failure. Because single ionophore treatment was used in only one previous cycle it cannot be ruled out that some improvement in clinical outcomes would also have been achieved by using single instead of double ionophore treatment again in the subsequent attempt.